Development of critical thinking of students – future biotechnologists in the process of teaching mathematics - S. I. Toropova (Образование и наука)
Introduction. In the context of the availability of information containing misleading arguments, the prevalence of electronic devices and the Internet, there is the increasing demand for the ability to effectively navigate the information field, to establish cause-and-effect relationships, to formulate one’s own conclusions and to make informed decisions. Consequently, one of a modern university graduate’s key competencies is critical thinking, which influences students’ adaptation in society and their professional realisation. Critical thinking development is an urgent task in the process of mathematical education of students, who plan to work in areas directly related to the well-being of future generations.Aim. The current research aims to identify and test the methodological conditions that ensure the development of critical thinking of students – future biotechnologists in the process of teaching mathematics at the university. An additional task was the development of diagnostic tools aimed at assessing critical thinking skills.Methodology and research methods. The research involved 81 students of the Vyatka State University majoring in 19.03.01 Biotechnology training programme. The main methods for measuring critical thinking, presented by the UF/EMI Critical Thinking Disposition Instrument and the Critical Thinking Barriers Scale (CTBS), were supplemented with diagnostic tools from specially designed tasks, taking into account the specifics of teaching mathematics to future biotechnologists. Statistical analysis of the obtained results was performed using the Mann-Whitney U test.Results and scientific novelty. For the first time, on the basis of modern research, the features of the formation and evaluation of critical thinking of students – future biotechnologists in the process of teaching mathematics are presented. A number of methodological conditions, which ensure the development of this type of thinking, are formulated. The conditions clarify and expand the ideas about the system of mathematical training of bachelors-biotechnologists. Diagnostic tools were developed and tested. Its key feature is that the student does not work in a simulated environment, but on real problems. The intervention effectiveness based on the described conditions was confirmed by significant differences (Uemp.= 128 < Ucr.= 142; p < 0,01).Practical significance. The identified methodological conditions and the proposed diagnostic tools can be used to improve the mathematical training of future biotechnologists, as well as to optimise the process of teaching mathematics in order to develop the main components of critical thinking.